UNDERSTANDING THE EQUALITY OF TWO SPECIES OF GOATFISH - S. K. Verma (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2015)
The goatfish genus Upeneus (Mullidae) must be investigated more extensively since there is a potential that previously unknown species might exist in less well explored places. Specifically, this study is focused on the SWIO as well as the so-called japonicus-group of Upeneus, which is a taxonomic species group in its own right. During a recent visit to Sodwana Bay in KwaZulu–Natal, South Africa, researchers discovered and collected the newly described Floras goatfish, U. floras, which they named after the Floras River in Italy. All 13 japonicus-group taxa were compared based on their colour patterns and morphological traits, as well as their COI barcoding results. In the coastal region between Angoche, N Mozambique, and KwaZulu-Natal, the new species partially overlaps with two other similar species, U. guttate, which is widely distributed in the Indo-West Pacific, and U. saiab, which is considered to be endemic to a small area off the coast of Angoche, South Africa. Further comparisons were made between U. Seychellois’s from the Seychelles Bank and U. Pori from the Mediterranean (in the form of a Lessepsian migrant), the Northern Red Sea, and Madagascar as additional japonicus-group species in the SWIO. New taxonomic descriptions and diagnoses of the two previously misdiagnosed species, U. floras and U. guttatus, are provided, taking into account the size and population differences of the species, respectively. It has been reported that three specimens of U. pori from NE Madagascar have been discovered, as well as a newly discovered colour photograph of a previously known species from SW Madagascar. Upeneus floras is distinguished from Upeneus guttatus and Upeneus pori by the length of its head, the height of its first dorsal fin, and the number of gills rakers on its gills. There are many distinguishing characteristics between Upeneus guttatus and the other two species, including disproportionally bigger anterior dorsal-fin spines, yellow or creamy-white barbless, and fewer pectoral fin rays. When COI barcoding was utilised, however, it was discovered that there was no significant divergence between U. guttatus, U. floras, and U. pori.